2020
DOI: 10.1039/d0sc04442c
|View full text |Cite
|
Sign up to set email alerts
|

Triboluminescence of a new family of CuI–NHC complexes in crystalline solid and in amorphous polymer films

Abstract: Triboluminescent compounds that generate emission of light in response to mechanical stimulus are promising targets in the development of “smart materials” and damage sensors. Among triboluminescent metal complexes, rare-earth europium...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…[166,[172][173][174][175][176] Recently, Karimata et al reported a family of Cu-NHC complexes that show bright TL in the crystal state in ambient indoor light under air. [177] It was found that the samples after mechanical grinding have not shown aggregation effect on the crystal packing, which is contrast to some other known organic TL materials. It was proposed that the generation of oppositely charged planes in ionic crystalline compounds upon fracture, or the presence of defects or disorders in the crystal structure leading to local noncentrosymmetry were the possible reasons for the TL effect.…”
Section: Mechanochromic Energy Conversionmentioning
confidence: 86%
“…[166,[172][173][174][175][176] Recently, Karimata et al reported a family of Cu-NHC complexes that show bright TL in the crystal state in ambient indoor light under air. [177] It was found that the samples after mechanical grinding have not shown aggregation effect on the crystal packing, which is contrast to some other known organic TL materials. It was proposed that the generation of oppositely charged planes in ionic crystalline compounds upon fracture, or the presence of defects or disorders in the crystal structure leading to local noncentrosymmetry were the possible reasons for the TL effect.…”
Section: Mechanochromic Energy Conversionmentioning
confidence: 86%
“…Considering that the previously reported ( R N4)Cu complexes containing halide and N-heterocyclic carbene ligands are photoluminescent, [25][26][27][28] we decided to investigate the photoluminescence properties of 4-6 and compare them to their Cu-acetonitrile precursors. Among copper-acetonitrile complexes 1-3, only the most sterically hindered complex 3 showed emission with an emission peak maximum at 619 nm and a photoluminescence quantum yield (PLQY) of 0.35 in the crystal state.…”
Section: Synthesis and Spectroscopic Properties Of ( R N4)cu-ethylene...mentioning
confidence: 99%
“…25,26 Some of these complexes were also shown to be photoluminescent, with PLQY highly dependent on fluxional behaviour and steric factors. [25][26][27][28] In this work, we report our studies of ethylene binding to a Cu I center supported by a tetracoordinate R N4 ligand. An unusual μ-η 2 -η 2 ethylene coordination was also found in the solid state, previously unreported for this metal and characterized by significant CvC bond elongation in the coordinated ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…However, many cases contradict the described theory. Indeed, there are compounds whose triboluminescent spectrum is identical to that of the photoluminescent one, but without any hint of gas excitation [ 18 ]. On the other hand, there are many piezoelectric materials in nature that do not exhibit triboluminescence at all [ 1 ].…”
Section: The (Un)known Mechanism Of Triboluminescencementioning
confidence: 99%
“…The crystallographic structure of a triboluminescent compound may have a crucial influence on the TL properties [ 18 ]. In the case of the described compound, the Cu + ion is surrounded by four electron-donor ligands: thiocyanate group, triphenylphosphine, and two pyridine molecules ( Figure 5 a,b).…”
Section: Chemical and Structural Analysismentioning
confidence: 99%